Preliminary Blood Pressure Screening in a Representative Sample of Extremely Obese Kuwaiti Adolescents - Rima Abdul Razzak; Asma Elmteri; Taiba Elkanderi; Fareedah Ishaq; Munera Eljasem; Saja AlDuraie; Jenan Al-Boloushi; Fatma Elbanay; Latifa Eldabos (Hindawi Limited, 2013)
A relationship between blood pressure (BP) and obesity has been found in young adults, but no data are available for adolescents in Kuwait. 257 adolescent (11-19 years) participants were categorized into two groups according to their BMI; 48 nonobese (21 males: 43.7% and 27 females: 56.3%) with mean age of years and 209 obese (128 males: 61.25% and 81 females: 38.75%) with mean age of years. The mean BMI was  kg/m2 for the nonobese group and  kg/m3 for the obese group. Most BP measures based on a single screening were significantly higher in the obese group. The prevalence of elevated BP was significantly higher in the obese subjects (nonobese: 13%; obese: 63%; ). In the obese group, there was a significant positive correlation between total sample BMI and all BP measures except the pulse pressure. There was a similar rate of elevated blood pressure between males and females (64% versus 60%; ). For both isolated systolic elevated BP and isolated diastolic elevated BP, the prevalences were comparable between the males (systolic: 42%; diastolic: 5%) and females (systolic: 34%; diastolic: 14%). Only systolic BP was positively correlated with BMI in obese adolescent males (Spearman ; ), with a significant correlation between BMI with diastolic (Spearman ; ) and mean BP (Spearman ; ) in females.